The book of lost things - Voigt, Cynthia; Bruno, Iacopo (New York : Alfred A. Knopf, 2013)
"When Max's parents leave the country without him, he must rely on his wits to get by, and before long he is running his own--rather unusual--business"--Provided by publisher.
Kirkus Starred
Publisher's Weekly
School Library Journal
Booklist, August 2013
Bulletin (Center for Children's books), September 2013
Horn Book, September 2013
Keywords: Problem solving -- Juvenile fiction; Self-reliance -- Juvenile fiction; Historical fiction; Mystery and detective stories; Problem solving -- Fiction; Self-reliance -- Fiction; Historical fiction; Mystery fiction; Problem solving -- Fiction; Self-reliance -- Fiction; Historical fiction; Mystery fiction